Conformer-dependent vacuum ultraviolet photodynamics and chiral asymmetries in pure enantiomers of gas phase proline - Rim Hadidi (Nature Portfolio, 2021)
Proline plays an important role in determining the structures of proteins and peptides, but the conformer landscape of proline is still not fully mapped. Here, the authors show the conformer-specific cation fragmentation and photoelectron circular dichroism of proline during its vacuum ultraviolet photoionization.